GAMBARAN PENGETAHUAN IBU TENTANG RUAM POPOK PADA BAYI 0-12 BULAN DI KLINIK BERSALIN HADIJAH TAHUN 2017 - ENNI YUSRIANI (JURNAL ILMIAH KOHESI, 2018)
Based on data released by the World Health Organization (WHO) in 2012 the prevalence of skin irritation (diaper rash) in infants was quite high, 25% of 6,840,507,000 babies born in the world mostly suffer from skin irritation (diaper rash) due to diaper use. The highest number is found at the age of 6-12 months. This study aims to determine the description of mother's knowledge about diaper rash in infants 0-12 months at Hadijah Maternity Clinic in 2012. The research is descriptive using primary data with the total population of all mothers who have 0-12 Months Babies who visit during Immunization at the Hadijah Maternity Clinic. 25 Respondents are Purposive Sampling techniques, with Data Collection methods using Data Analysis Questionnaires discussed with Theory and Existing library. From the results of the study of diaper rash in infants obtained from 25 respondents, the majority of good knowledge as many as 13 respondents (52%), based on maternal characteristics according to age The majority of age 20-35 years were 19 respondents (76%). Based on education, the majority of high school / vocational education were 12 respondents (48%). Based on the parity of the majority of primiparas, there were 13 respondents (75%). Based on the information source, the majority of information sources from electronic media were 11 respondents (44%). Based on the results of the study concluded that mothers who have 0-12 months babies who visited during immunization at the Hadijah Maternity Clinic were well-informed. it is expected that health workers will further improve counseling about diaper rash in infants for mothers and the community.